The Obstacles in the Rational Decision-Making Process of Economic Actors: Cognitive Biases and Mental Shortcuts - Aygün, İnci Z.; Aktas, Erkan (Journal of Applied And Theoretical Social Sciences, 2023)
Rationality, which is known as one of the basic assumptions of classical economics, has become quite controversial in time, especially with the emergence of behavioral economics on the stage of history. With the cooperation of psychology, which became an established discipline towards the end of the 19th century, with economics, the need to determine the anomalies behind economic behavior arose. Behavioral economics, which is an interdisciplinary approach, has started to investigate the reasons that affect the reasoning process of people and prevent them from exhibiting rational behavior. Cognitive biases and mental shortcuts that we can talk about as a systemic error in the person's thought process; prevents the person from acting rationally. While applying to cognitive processes while in the decision stage, it will sometimes lead to erroneous results, even if it promises convenience and practicality. The method of this study is a descriptive analysis, and behavioral anomalies that affect economic decision processes are tried to be explained. This study is a literature review, and in this sense, current theoretical and applied studies are presented and the reasons that push people to irrationality are explained. The aim of this study is the revealing of different behavioral anomalies that affect the thought process of people.